Lightning characteristics observed by lightning detection system (LDS) along KLMK-PROI 275 kV transmission line - Ali, Mohd Aldrin (2006)
A cloud-to-ground lightning activity data collected by a Lightning Detection System (LDS) along the 275 kV transmission line KLMK-PROI in year 2004 to 2005 from Seremban to Melaka has been investigated. The LDS are installed by TNB Research Sdn Bhd (TNBR) in 1994. Annual lightning days are acquired and ground flash density maps are constructed from the database. Lightning parameters such as, polarity, ground flash density and peak lightning current were analyzed with the lightning data collected by LDS. The lightning data was analyzed using FALLS (Fault Analysis and Lightning Location System) software. It is found that the negative lightning is observed more than the positive lightning. Also found that the value of peak current either negative or positive polarity is about 30 kA. The performance of LDS, especially detection efficiency, was evaluated using the data obtained from transmission line fault and lightning activities along transmission line. It is found detection efficiency is 93.38%.